A comprehensive 1000 Genomes–based genome-wide association meta-analysis of coronary artery disease - Nikpay, Majid; Goel, Anuj; Won, Hong-Hee; Hall, Leanne M; Willenborg, Christina; Kanoni, Stavroula; Kyriakou, Theodosios; Nelson, Christopher P; Harris, Tamara B; Hazen, Stanley L; Hengstenberg, Christian; Hofman, Albert; et al. (Nature genetics, 2015)
Hugh Watkins, Sekar Kathiresan, Ruth McPherson, Martin Farrall and colleagues report the results of a large genome-wide association meta-analysis of coronary artery disease based on 1000 Genomes imputation. They identify ten new risk loci and show that susceptibility to this disease is largely determined by common SNPs with small effect sizes. Existing knowledge of genetic variants affecting risk of coronary artery disease (CAD) is largely based on genome-wide association study (GWAS) analysis of common SNPs. Leveraging phased haplotypes from the 1000 Genomes Project, we report a GWAS meta-analysis of ∼185,000 CAD cases and controls, interrogating 6.7 million common (minor allele frequency (MAF) > 0.05) and 2.7 million low-frequency (0.005 < MAF < 0.05) variants. In addition to confirming most known CAD-associated loci, we identified ten new loci (eight additive and two recessive) that contain candidate causal genes newly implicating biological processes in vessel walls. We observed intralocus allelic heterogeneity but little evidence of low-frequency variants with larger effects and no evidence of synthetic association. Our analysis provides a comprehensive survey of the fine genetic architecture of CAD, showing that genetic susceptibility to this common disease is largely determined by common SNPs of small effect size.